(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
Many regard President Donald Trump as a master of whipping up fear to support his political agenda (e.g., Ball 2016). Perhaps like no other president, Trump creates scapegoats and bogeymen to shift direction from his own faults andfailings, to ignite his base of supporters, and to garner approval for repressivepolicies and practices. We’ve seen the president do this with immigrants, spewingand tweeting that they are all criminals who will take Americans’ jobs and soak our social services (e.g., Finley and Esposito 2020). His latest foil, amidst the protests by Black Lives Matter related to the murder of George Floyd and many other Black men, is Antifa.